Increased serum ATG5 as a marker of autophagy in psoriasis vulgaris patients: a cross-sectional study - Abu El-Hamd, Mohammed; Abdel-Hamid, Soheir; Hamdy, Aya-tollah; Abdelhamed, Amr (Archives of dermatological research, 2024)
Psoriasis (PsO) is a prevalent chronic inflammatory skin disease. It is a complex condition that is affected by environmental and hereditary variables. Numerous pathogens, including viruses, bacteria, and even fungi, have been linked to PsO. One of the mechanisms that clears infections is autophagy. The mechanism by which a cell feeds itself is called autophagy by reusing cytoplasmic components in the lysosome. The autophagy-related (ATG) proteins are essential components of the system that control the strictly regulated process of autophagy. Among these 41 proteins, ATG5 is one that is required in order for autophagic vesicles to develop. This research aimed to compare ATG5 levels in serum among those suffering from psoriasis vulgaris and healthy controls. This cross-sectional research was carried out on 45 individuals with vulgaris psoriasis and 45 healthy, sex and age-matched control subjects. All participants underwent a clinical examination, a laboratory investigation, and a history taking, including lipid profiles and serum ATG5. The mean age of the control and PsO were 40.6 ± 9.6, and 43.7 ± 9.3 years respectively. The mean total PASI score was 13.9 ± 8.9, with a median of 11.7 (8.8). According to the PASI score, about 38% (n = 17) had mild disease (PASI < 10), and about 62% (n = 28) had moderate/severe disease (PASI ≥ 10). There was a significantly higher median (IQR) (25th–75th) ATG5 level in PsO 206 (97) (145–242) ng/ml than in the control 147 (98) (111–209) ng/ml (p = 0.002). An insignificant higher median level (IQR) was observed in PsO with mild disease 207(95) compared with those with moderate/severe disease 183(98.5) (p = 0.057). Dissimilarly, the median (IQR) ATG5 level was significantly lower in PsO individuals with metabolic syndrome 170(72) compared with those without 207(104) (p = 0.044). Four predictors were identified following sex and age adjustments, in the final linear regression model: PASI score, triglyceride, High-Density Lipoprotein, and presence of metabolic syndrome. There can be a connection between autophagy as measured by ATG5 and psoriasis vulgaris. ATG5 was elevated in the serum of individuals with psoriasis vulgaris. However, it decreased in patients with metabolic syndrome. No relation was found between serum ATG5 and PASI score. Psoriasis vulgaris patients may benefit from using an autophagy enhancer as a potential treatment target.